THE ROLE OF SERVICE ACTIVITIES IN THE OIL AND GAS SECTOR AND TRENDS IN THEIR DEVELOPMENT - Кузнєцов, Андрій Ігорович; Zapukhliak, Ivanna Bogdanivna (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2025)
The article presents a comprehensive study of service activities in the oil and gas sector as a key component ensuring the efficiency, continuity, and innovativeness of production and technological processes. It is determined that service activities encompass a wide range of operations—from technical maintenance and engineering support to logistics, administrative, environmental, and safety solutions. Based on the systematization of processes that form the complete production cycle of the oil and gas industry, a classification of service activities has been developed, including technological, engineering, logistical and material-support services, administrative and managerial services, as well as environmental and safety services. The application of analytical and systemic approaches made it possible to consider the service segment as an integral part of the organizational and production structure of enterprises and to determine its role within the value chain “upstream–midstream–downstream”. A comparative analysis of national and international practices revealed key trends in the development of service activities, including the digitalization of production processes, the active implementation of artificial intelligence, modernization of technical solutions, increased attention to environmental safety, and the growing need to comply with ESG standards. A significant factor driving the transformation of the service market is the rising competition between domestic and international companies, which stimulates innovation, improves service quality, and fosters the emergence of new business models, particularly servitization and the expansion of outsourcing practices. The article outlines the prospects for the development of the service segment of Ukraine’s oil and gas sector, such as the growing role of digital services, strengthened environmental sustainability, accelerated development of energy transition services (hydrogen, renewable energy sources, CCUS), and the enhancement of international partnerships. Potential challenges are also identified, including the need for substantial investments, a shortage of highly qualified specialists, and tightening regulatory requirements. The study forms a scientific basis for further research focused on forecasting the development of the oil and gas service market and assessing its impact on the strategic resilience of the industry.